Neuroproprioceptive facilitation techniques. Practical applications for the upper limb - IANC, Dorina; DEAC, Anca (Presa Universitară Clujeană, 2020)
Proprioceptive neuromuscular facilitation (PNF) uses the body’s proprioceptive system to ease or inhibit muscle contraction. These techniques are based on Sherrington’s reciprocal inhibition, innervation and irradiation principles (1). PNF techniques were developed in the 1940-1950 and they are the result of Kabat’s, Knott’s and Voss’s work (1, 2). They combine the research of functional movement with theories of motor development, motor control, motor learning and neurophysiological theories (3). Harman Kabat first used the PNF techniques on young people with cerebral palsy and other neurological disorders (2, 4). D. Voss defines neuroproprioceptive facilitation as a promotion or acceleration method of the neuromuscular system’s response by proprioceptors’ stimulation. The muscles must work in synergy in order to achieve the movement. This requires that the muscles should have the reflex capacity of contraction and relaxation to perform the basic movement. The basis of functional training is the ability to create a balance between mobility and stability (5).